Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Let's determine the expressions [tex]\((g - h)(x)\)[/tex] and [tex]\((g + h)(x)\)[/tex], and evaluate [tex]\((g \cdot h)(-1)\)[/tex] for the given functions [tex]\(g(x)\)[/tex] and [tex]\(h(x)\)[/tex].
1. Expression for [tex]\((g - h)(x)\)[/tex]
Given:
[tex]\[ g(x) = x + 3 \][/tex]
[tex]\[ h(x) = 4x^2 \][/tex]
To find [tex]\((g - h)(x)\)[/tex], we subtract [tex]\(h(x)\)[/tex] from [tex]\(g(x)\)[/tex]:
[tex]\[ (g - h)(x) = g(x) - h(x) \][/tex]
[tex]\[ (g - h)(x) = (x + 3) - 4x^2 \][/tex]
Therefore:
[tex]\[ (g - h)(x) = -4x^2 + x + 3 \][/tex]
2. Expression for [tex]\((g + h)(x)\)[/tex]
To find [tex]\((g + h)(x)\)[/tex], we add [tex]\(g(x)\)[/tex] and [tex]\(h(x)\)[/tex]:
[tex]\[ (g + h)(x) = g(x) + h(x) \][/tex]
[tex]\[ (g + h)(x) = (x + 3) + 4x^2 \][/tex]
Therefore:
[tex]\[ (g + h)(x) = 4x^2 + x + 3 \][/tex]
3. Evaluate [tex]\((g \cdot h)(-1)\)[/tex]
To find [tex]\((g \cdot h)(-1)\)[/tex], we multiply [tex]\(g(-1)\)[/tex] and [tex]\(h(-1)\)[/tex].
First, calculate [tex]\(g(-1)\)[/tex]:
[tex]\[ g(-1) = (-1) + 3 = 2 \][/tex]
Next, calculate [tex]\(h(-1)\)[/tex]:
[tex]\[ h(-1) = 4(-1)^2 = 4 \cdot 1 = 4 \][/tex]
Now, multiply [tex]\(g(-1)\)[/tex] and [tex]\(h(-1)\)[/tex]:
[tex]\[ (g \cdot h)(-1) = g(-1) \cdot h(-1) \][/tex]
[tex]\[ (g \cdot h)(-1) = 2 \cdot 4 = 8 \][/tex]
Summarizing the results:
[tex]\[ (g - h)(x) = -4x^2 + x + 3 \][/tex]
[tex]\[ (g + h)(x) = 4x^2 + x + 3 \][/tex]
[tex]\[ (g \cdot h)(-1) = 8 \][/tex]
1. Expression for [tex]\((g - h)(x)\)[/tex]
Given:
[tex]\[ g(x) = x + 3 \][/tex]
[tex]\[ h(x) = 4x^2 \][/tex]
To find [tex]\((g - h)(x)\)[/tex], we subtract [tex]\(h(x)\)[/tex] from [tex]\(g(x)\)[/tex]:
[tex]\[ (g - h)(x) = g(x) - h(x) \][/tex]
[tex]\[ (g - h)(x) = (x + 3) - 4x^2 \][/tex]
Therefore:
[tex]\[ (g - h)(x) = -4x^2 + x + 3 \][/tex]
2. Expression for [tex]\((g + h)(x)\)[/tex]
To find [tex]\((g + h)(x)\)[/tex], we add [tex]\(g(x)\)[/tex] and [tex]\(h(x)\)[/tex]:
[tex]\[ (g + h)(x) = g(x) + h(x) \][/tex]
[tex]\[ (g + h)(x) = (x + 3) + 4x^2 \][/tex]
Therefore:
[tex]\[ (g + h)(x) = 4x^2 + x + 3 \][/tex]
3. Evaluate [tex]\((g \cdot h)(-1)\)[/tex]
To find [tex]\((g \cdot h)(-1)\)[/tex], we multiply [tex]\(g(-1)\)[/tex] and [tex]\(h(-1)\)[/tex].
First, calculate [tex]\(g(-1)\)[/tex]:
[tex]\[ g(-1) = (-1) + 3 = 2 \][/tex]
Next, calculate [tex]\(h(-1)\)[/tex]:
[tex]\[ h(-1) = 4(-1)^2 = 4 \cdot 1 = 4 \][/tex]
Now, multiply [tex]\(g(-1)\)[/tex] and [tex]\(h(-1)\)[/tex]:
[tex]\[ (g \cdot h)(-1) = g(-1) \cdot h(-1) \][/tex]
[tex]\[ (g \cdot h)(-1) = 2 \cdot 4 = 8 \][/tex]
Summarizing the results:
[tex]\[ (g - h)(x) = -4x^2 + x + 3 \][/tex]
[tex]\[ (g + h)(x) = 4x^2 + x + 3 \][/tex]
[tex]\[ (g \cdot h)(-1) = 8 \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.